PowToon software's impact on EFL students' writing of narrative text - Muniroh, Rima Zahrotul; Maharani, Mega Mulianing; Anwar, Choiril; Ekaningsih, Nur (EduLite: Journal of English Education, Literature and Culture, 2023)
The development of technology brings challenges for teachers to be more innovative and creative in delivering materials. Teachers need to explore currently medium for teaching. To assist teachers and students in overcoming their difficulties, PowToon Software was chosen. The goal of this study was to find out whether PowToon as a learning media was effective in improving the narrative text writing ability of grade XI students at SMA Negeri 1 Pegandon in the 2023/2024 academic year. This study used a quasi-experimental method. The sample consisted of grade XI 1 students as the control group and XI 2 as the experimental group. The control group and experimental group completed the pre-test and post-test. Data analysis in the study used SPSS. The results showed a significance improvement in students' writing achievement. This was evidenced by the significance value of 0.003. The value was smaller than 0.05 and this means that H0 was rejected and H1 was accepted. It can be summarized that the use of PowToon Software as a learning media was effective to improve students' narrative text writing ability.